Analisis Penerapan Kurikulum Merdeka Belajar Untuk Meningkatkan Kemampuan Siswa Kelas 4 Pada SD Negeri Pangkalan - Suanah Suanah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2023)
Learning activities with the implementation of the independent learning curriculum focus on freedom in creative and independent thinking to create a fun learning atmosphere. The aim of the research is to analyze the application of the independent learning curriculum to improve students' abilities. Research time in the odd semester of the 2022/2023 academic year. Sources of research data from informants based on purposive sampling technique. Methods of data collection using interviews, observation, document analysis and literature review. The data processing stage classifies and identifies problems. The stages of analysis formulate the results of implementing the independent learning curriculum. The results of the analysis in aspect that is the training has been attended by teachers and education staff. The necessary infrastructure includes learning media, textbooks, computers, infocus, internet networks, libraries and green open spaces. The implementation step is to map capabilities, classify capabilities and determine the type of service. Constraints are still not available on the internet network and learning media. Students are still not familiar with the learning methods in the independent learning curriculum. The impact on students' IQ, EQ and SQ abilities becomes more developed. The challenge for teachers is to take the time to provide services according to the classification of students' abilities.